(untitled) (The Review of Diabetic Studies, 2024)
Background: A common and significant issue that affects the urinary system as a result of dietary and lifestyle changes is kidney stones. The management of self-care has a significant impact on patients’ health. . Aim of the study: Was to assess self-care management of kidney stones Saudi patients. Design: A descriptive research design. Settings: This study was conducted at Urology Outpatient Clinics of University Hospital, Saudi Arabia. Sampling: A convenient sample of kidney stone patients who attending in previously mentioned setting for six months (200 patients). Data collection tools: Two tools were used to conduct this study; I. A structured interviewing questionnaire. II. Kidney stone patients’ practices about self-care management. Results: More than two fifths of the studied patients had poor total knowledge about kidney stone. While more than one third of them had average total knowledge about kidney stone. Less than three quarters of the studied patients had average total score of self-care pattern. While almost one fifth of them had good total score of self-care pattern. Conclusions: There was highly statistically significant relation between studied patients’ demographic characteristics and their total knowledge score moreover; there was highly statistically significant relation between studied patients’ demographic characteristics and their total score of self-care pattern. Less than three quarters of studied patients had average total score of self-care pattern and less than half of studied patients had poor total knowledge about kidney stone. Recommendations: Developing and implementing educational program for kidney stone patients to improve self-care management.